Secure recovery : approaches to recovery in forensic mental health settings - Drennan, Gerard; Alred, Deborah (Abingdon [England] ; New York : Routledge, 2012)
"Secure Recovery is the first text to tackle the challenge of recovery-oriented mental health care in forensic services and prison-based therapeutic communities in the UK. Recovery as an emergent paradigm in the field of mental health presents a challenge to all services to embrace a new clinical philosophy, but nowhere are the implications more profound than in services that are designed to meet the needs of mental disordered and personality disordered offenders, both men and women. The chapters collected together in this book represent a cross-section of experiences in high, medium and low secure services and prison-based therapeutic communities in England and Scotland that have begun to implement a recovery-orientation to the rehabilitation of offenders with mental health needs. Secure Recovery sets out a road map of guiding principles, practical and evidence-based strategies for promoting service user participation in their care and treatment and further demonstrates the adaption of traditional treatment approaches, and the development of innovations in rehabilitation, as well as tackling training for staff teams, and the evaluation of service delivery. This book provides a valuable resource and an inspiration to practitioners working across forensic mental health settings, increasing understanding of contemporary challenges and suggesting ways of moving forward"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Mentally ill prisoners -- Mental health services -- Great Britain; Prisoners -- Mental health services -- Great Britain; Mentally ill offenders -- Rehabilitation -- Great Britain; Electronic books